Frustration Intolerance, Self-Efficacy and Sleep Quality in Medical Students During Pandemic of Covid-19 - Shafqat Huma, Muhammad Fahim Qasim, Muhammad Asif Kamal, Fatima Aamir Khan, Nadia Naveen (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: A novel coronavirus disease (COVID-19) was initially reported in China in December 2019. In a few months, the virus spread rapidly across the globe, and on 30 January 2020 the World Health Organization (WHO) declared the outbreak to be a Public Health Emergency of International Concern. Objectives: The main objective of the study is to find the frustration intolerance, self-efficacy and sleep quality in medical students during pandemic of COVID-19. Material and methods: This cross sectional study was conducted in University of Lahore during 2021-2022. The data was collected through questionnaire. The questionnaire covered sleep conditions, stores of infection control supplies, mood and stress, usage of social media and sources of acquiring COVID-19 information, risk perception, and sociodemographic data. Results: The data was collected from 200 patients. About half of them were young-aged (55.0%) and married (49.1%). In terms of social media use, 57.8% spent more than 2 h per day. With regard to sleep deterioration after the COVID-19 outbreak, the weighted proportions of those who reported worsening sleep quality, worsening sleep initiation, and shortened sleep duration were 38.3%, 29.8%, and 29.1%, respectively. The weighted prevalence of current clinical insomnia was estimated at 29.9%. Practical implication: This study will help to find out the effect of COVID-19 on sleep quality, sleep initiation and duration among Pakistani population. Conclusion: It is concluded that COVID-19 is widely spreading in Pakistan and it effects on their sleep quality, sleep initiation, and sleep duration had worsened since the outbreak of COVID-19. This study identified high prevalence of frustration intolerance and poor sleep quality in medical students during pandemic of Covid-19. Keywords: COVID-19, Prevalence, Frustration, Pakistan, Sleep, Identify